Cystoid Macular Edema in Acute Presentation of Central Retinal Artery Occlusion. (4th April 2012) - Ng, Wei Yan; Wong, Doric W. K.; Yeo, Ian Y. S.; Han, Daphne C. Y.
Abstract : A seventy-six-year-old lady with poor vision of the left eye due to previous retinal detachment presented with acute visual loss of her right eye secondary to central retinal artery occlusion. Clinical examination showed a pale right optic disc, macular edema, and a cherry red spot. Optical coherence tomography done four hours after onset showed right acute cystoid macular edema and diffuse inner retinal thickening. Subsequent treatment with intravenous carbonic anhydrase inhibitor resulted in some visual improvement. Central retinal artery occlusion has been known to produce diffuse intraretinal edema instead of cystoids changes. We would like to discuss a case of acute cystoid macular edema in acute central retinal artery occlusion.